Respuestas
Respuesta dada por:
0
x²-5x-84 = 0
x = {5+-√(-5²-4*1*-84)} / 2*1
x = {5+-√(25+336)} / 2
x = {5+-√361}/2
x = {5+-19}/2
x₁ = {5-19}/2 = -14/2 = -7
x₂ = {5+19}/2 = 24/2 = 12
Saludos........
x = {5+-√(-5²-4*1*-84)} / 2*1
x = {5+-√(25+336)} / 2
x = {5+-√361}/2
x = {5+-19}/2
x₁ = {5-19}/2 = -14/2 = -7
x₂ = {5+19}/2 = 24/2 = 12
Saludos........
Respuesta dada por:
1
Solución:
x² - 5x - 84 = 0
x 7 -----> (x + 7)
x -12 -----> (x - 12)
⇒ (x + 7)(x - 12) = 0
Entonces:
x + 7 = 0 x - 12 = 0
x = -7 x = 12
RTA:
x = {-7 , 12}
x² - 5x - 84 = 0
x 7 -----> (x + 7)
x -12 -----> (x - 12)
⇒ (x + 7)(x - 12) = 0
Entonces:
x + 7 = 0 x - 12 = 0
x = -7 x = 12
RTA:
x = {-7 , 12}
Preguntas similares
hace 7 años
hace 9 años
hace 9 años
hace 9 años